Perspektif HAM dalam Pemulihan Kegiatan Usaha bagi Masyarakat Ekonomi Lemah di Daerah Pasca Gempa - Rahjanto Rahjanto; Yuliana Primawardani (Jurnal HAM, 2013)
The impact of natural disasters directly affect the livelihood of the people in the area after the earthquake. States should make efforts in accordance with the real situation in the area and emergency conditions after the earthquake . This includes implementing restoration projects of economic activity, including the opportuni- ties and livelihood are disrupted by natural disasters, should begin immediately. The study used a qualitative approach. Data collection was conducted in 5 provinces, namely Bengkulu; West Java; West Sumatra; Aceh; Yogyakarta. Partnership with central government and local government agencies, or other agencies in the recovery of business activity so that people more easily determine which line of business can be carried out in accordance with theirsa expertise before the earthquake. Field findings indicate recovery operations for the poor economic people in the region after the earthquake in the repair of facilities, provision of capital and the provision of tools that are used for subsistence. Obstacles encountered in each of the provinces affected by the earthquake have almost the same problem, namely the unclear division of tasks between the Regional Disaster Management Agency (BPBD), Social Services, Department of Public Works.